(thf)(2)Ln(Ge-9Si(SiMe3)(3) - Klementyeva, Svetlana V.; Schrenk, Claudio; Zhang, Minghui; Khusniyarov, Marat; Schnepf, Andreas (Chemical Communications)
We report the synthesis, structure and magnetic properties of the first rare earth complexes of metalloid group 14 clusters [(thf)(2)Ln(Ge(9)Hyp(3))(2)] (Ln = Eu, Sm, Hyp = Si(SiMe3)(3)). X-Ray crystallographic analysis and DFT calculations reveal a novel eta(2)-coordination mode of the Ge(9)Hyp(3) units and a slight distortion of the Ge-9 cage.
CRIS-Team WoS Importer:2021-05-07